The effects of haptonomy and virtual reality, anxiety, prenatal attachment and acceptance of pregnancy in unplanned pregnancy - Yilmaz, Ayse Nur; Derya, Yesim Aksoy (Routledge Journals, Taylor & Francis Ltd, 2025)
Aim: Unplanned pregnancies are an important public health problem that negatively affects the health of women and babies. This study aimed to determine the effects of haptonomy and virtual reality on anxiety, prenatal attachment and acceptance of pregnancy in unplanned pregnancies. Haptonomy, a touch-based bonding technique, and virtual reality, an immersive fetal visualisation tool, were used as interventions. Methods: The sample of this randomised controlled study consisted of 217 pregnant women (haptonomy: 73, virtual reality: 72 and control: 72) who applied to the Obstetrics and Gynaecology outpatient clinics of a public hospital in eastern Turkey between July 2020 and April 2021. For both experimental groups, four interviews were conducted with the pregnant women between the 24thand32nd gestational weeks at intervals of 7-10 days. Data were collected on pregnancy-related anxiety, prenatal attachment and pregnancy acceptance. Group differences were analysed using appropriate statistical comparisons. Results: Pregnancy-related anxiety was lower, and acceptance of pregnancy was higher in the experimental groups compared to the control group (p < .001). Prenatal attachment level was higher in the haptonomy and virtual reality groups compared to the control group (p < .001). Notably, prenatal attachment scores were significantly higher in the haptonomy group compared to the virtual reality group (p < .001). Conclusion: In unplanned pregnancies, imagining the baby through haptonomy and imagining the baby through virtual reality are techniques that reduce the level of anxiety related to pregnancy and increase the level of prenatal attachment and acceptance of pregnancy. Especially haptonomy showed a higher effect on prenatal attachment.
Keywords: Anxiety; haptonomy; midwifery; prenatal attachment; unplanned pregnancy; virtual reality